GROWTH RELATIONSHIPS AND REPRODUCTIVE FEATURES OF Sarotherodon galilaeus (Linnaeus, 1758) IN ELEIYELE LAKE SOUTHWESTERN NIGERIA - AYOADE, A. A.; ONIBONOJE, K. O. (Nigerian Journal of Fisheries, 2013)
Length weight relationship (LWR), condition factor (K) and some reproductive features of Sarotherodon galilaeus Linnaeus, 1758 from Eleiyele Lake were investigated from March, 2010 to February 2011.Total length and weight were recorded. Gonad maturation was determined macroscopically, fecundity by gravimetric method and gonadosomatic indices calculated. The LWR had a significant correlation for the sizes, sexes and seasons. Differences were recorded in the growth pattern between size groups and sexes. The species was in good condition in the Eleiyele Lake with K greater than 1. Higher gonadosomatic index recorded between August and December suggests that spawning occurred during this period. Fecundity of S. galilaeus ranged from 572 – 4082 for a fish with total length 13.4 – 21.4 cm. The information provided on the growth pattern and reproductive features of this commercially important species (Sarotherodon galilaeus, which is little studied in Eleiyele Lake) should enhance effective management of the fisheries and production.